OCCUPATIONAL HEALTH AND SAFETY MANAGEMENT IN CIUDAD DEL ESTE SMES - Leticia Fariña, Elida; Johana Calbette, Francisca; Areco Martínez, Verónica (Revista Gênero e Interdisciplinaridade, 2023)
The present work deals with the Safety and Health System of small and medium-sized companies, specifically service stations, analyzes the different actions in terms of prevention and management of the different types of risks to which employees are exposed. workers, which includes a whole structure by which these types of companies must be governed, mandatory practices, procedures, resources to develop, prevention policies, tools and necessary training. Compliance with labor laws and regulations established by SMEs that each employer and worker must comply with, the organizational climate focused on safety and the perception of each employee about the job position and the safety measures used. For data collection, a survey has been applied, selecting for the sample, 50% of the chosen population, which is equivalent to 25 company workers, belonging to service stations in Ciudad del Este, specifically Puma, Petropar and Integral. . The results of the survey reveal the state of the health and safety system used by companies and the degree of security that workers feel in their jobs, thus being able to adopt the necessary preventive measures for each case.